Exploring the Metabolome and Antimicrobial Properties of Capsicum annuum L. (Baklouti and Paprika) Dried Powders from Tunisia - Annalisa Serio; Francesca Maggio; Anis Ben Hsouna; Rania Ben Saad; Cosimo Taiti; Stefania Garzoli (Molecules)
In this study, for the first time, the volatile fraction from two domesticated Capsicum annuum accessions (“Paprika” and “Baklouti”) collected in Tunisia was investigated by two complementary analytical techniques, such as Solid-Phase Microextraction–Gas Chromatography/Mass Spectrometry (SPME-GC/MS) and Proton Transfer Reaction–Time-of-Flight–Mass Spectrometry (PTR-ToF-MS). The obtained results highlighted the presence of a high number of Volatile Organic Compounds (VOCs), including monoterpene and sesquiterpene compounds with α-curcumene, I-zingiberene, β-bisabolene and β-sesquiphellandrene as the major components. In addition, GC/MS was used to investigate the non-volatile chemical composition of the dried powders and their extracts, which were found to be rich in sulfur compounds, fatty acids and sugars. Eleven bacterial strains were chosen to assess the antimicrobial effectiveness of the extracts. The results showed that the extracts exhibited strain-dependent behavior, and the type strains displayed a greater susceptibility to the treatments, if compared to the wild strains, and, in particular, showed the best antimicrobial activity against Gram-positive bacteria, such as Listeria monocytogenes and Staphylococcus aureus.